Islamic State of Afghanistan : First Review Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2004)
This paper assesses the First Review Under the Staff-Monitored Program (SMP) for Afghanistan. The authorities have met all of the indicative quantitative targets set out under the SMP and all the structural benchmarks, except the benchmark on licensing of commercial banks, which was only partly met owing to the opposition of the shareholders of Export Promotion Bank to its merger with three other state-owned banks. The IMF staff views the authorities' performance in the first quarter as a notable achievement.